Pengembanngan Bahan Ajar Sistem Persamaan Linear Dua Variabel Dengan Pendekatan Scientific Berbasis Website Untuk Membelajarkan Kemampuan Pemecahan Masakah Matematika Siswa - Ahmad, Marzuki; Siregar, Eva Yanti; Ndraha, Bagus Hasudungan (JURNAL MathEdu (Mathematic Education Journal), 2025)
This development research aims to 1) Knowing the validity of developing website-based twovariable linear equation system teaching materials, 2) Knowing the practicality of using web-based twovariable linear equation system development teaching materials in learning activities, and 3) Knowing the effectiveness of developing linear equation system teaching materials two website-based variables to teach students' mathematical problem solving skills. This research is a Research and Development (R&D) research with the ADDIE development model, where this research consists of 5 stages, namely, 1) Analysis Phase, 2) Design Phase, 3) Development Phase, 4) Implementation Phase and 5) Evaluation Phase. The instruments used include 1) a questionnaire sheet in the form of a validation questionnaire by an expert to see the validity of the product and student response questionnaires to see the practicality of the product, as well as 2) a test sheet to test the effectiveness of the developed product being tested on 24 students in class X MIA 1 SMA N 1 Angkola East. Based on the results of this study, the product validity was obtained with an average percentage of 89% in the " Valid" category, product practicality with an average percentage of 85% in the "Practical" category, and product effectiveness with an average percentage of 79,74% with the category "Effective".It can be concluded that the development of website-based two-variable linear equation system teaching materials to teach students' mathematical problem solving skills is valid, practical and effective.